(untitled) (Bulletin of Innovative Research, 2026)
This article examines the continuation of the classical humanistic tradition of Persian-Tajik literature in the poetry of Loiq Sherali. The aim of the study is to identify the features of continuity and creative reinterpretation of humanistic ideas in the modern poet’s poetics. The methodology is based on comparative-historical analysis, poetic analysis, and an intertextual approach. The poetry of Saadi, as a representative of the classical tradition, is compared with selected poems by Loiq Sherali. The findings demonstrate that Sherali does not merely imitate the classical humanistic tradition but creatively reinterprets it, enriching it with the socio-historical context of the twentieth century. In his poetry, the image of the human being appears as an ethical and socially responsible subject, while humanity is presented as a fundamental cultural value and a criterion for social continuity.